Environmental History For School - Hanim, Fitriah (HISTORIKA, 2020)
The history lessons that have existed in the school curriculum generally only discuss the development of the times, occupation, the struggle for independence, and social, political, economic and cultural changes (government). All of these factors discussed are about human life and human interests. Based on these problems, in the curriculum of history subjects especially at the high school level it is necessary to add environmental education using the Ecopedagogy approach that is expected from this, students can have ecological intelligence such as empathizing with all forms of life, anticipating undesirable natural conditions, reducing natural damage, protecting cleanliness, understanding how nature supports human life, and how the symbiosis of mutualism between humans and nature if humans are able to protect it. So that through history lessons in the context of environmental education using the ecopedagogy approach can reduce environmental damage, natural damage that goes on by nature does not get better but is increasingly damaged.